IMPLEMENTATION OF REGISTRATION POLICY FOR TRANSFER OF LAND RIGHTS DUE TO SALE AND PURCHASE IN POHUWATO REGENCY - Ruiba, Lupita; Zuchri Abdussamad; Rustam Tohopi (Journal of Governance and Public Administration, 2024)
The purpose of this study is to determine how communication, resources, disposition and bureaucratic structure in the Implementation of Land Rights Transfer Registration Policy Due to Sale and Purchase. This research was conducted at the Pohuwato Regency Land Office for 3 months from October 2023 to December 2023. This research is a descriptive research with a qualitative approach. This descriptive research is used because researchers try to photograph events that occur, researchers do not provide treatment or manipulation, but describe a condition as it is. The focus of this research is based on the policy implementation model proposed by the George C. Edward III Model. 4 (four) variables that affect policy implementation, namely communication, resources, disposition, and bureaucratic structure. The results showed that the implementation of the Land Rights Transfer Registration Policy due to Sale and Purchase at the Pohuwato Regency Land Office has run optimally, this can be seen from the existence of good communication, the availability of adequate resources, the characteristics of good implementors, and the existence of bureaucratic structures that have been running according to the Standard Operating Procedures (SOP) of the Pohuwato Regency Land Office.